The Potential Uses of Curcumin and PMSG Hormones to Increase Egg Production of Muscovy Ducks through Increasing Estradiol Concentrations and Shortening Laying Rest Period - Dwi Gunadi; Rukmiasih Rukmiasih; Wasmen Manalu (ANIMAL PRODUCTION, 2021)
The aim of this research was to study the effects of curcumin administration, injection of PMSG hormone, and the combination of curcumin supplementation and PMSG injection on the physiological parameters and performance of female Muscovy ducks. The objects of this research were 40 young female Muscovy ducks, aged 24 weeks, subjected to treatments: control (P1), curcumin supplementation at a dose of 24 mg/100 g feed (P2), intramuscular injection of PMSG hormone at a dose of 0.015 mL/hen (P3), and the combination of curcumin and PMSG (P4). The results showed that the treatment gave nonsignificant improvements in Muscovy duck performances, including feed consumption, egg production, and the day of laying period and molting period. Treatment gave a significant increase in serum estradiol concentration at molting period after treatment. This study concluded that the treatment provides no significant improvement in the performance of female Muscovy ducks because the genetic diversity of Indonesian ducks remains high.